The Influence of Consumer Behavior After COVID-19 Pandemic on Use of Digital Wallets in Gorontalo - Armayani Arsal; Setia Ningsih (Jurnal Ekonomi Islam, 2023)
This research is a descriptive quantitative research type, with the aim of looking at the influence of consumer behavior during the COVID-19 pandemic on the use of digital wallets in Gorontalo. The variables used are cultural, social, personal, and psychological. The data used are primary data obtained through a questionnaire with a total of 50 respondents. The data are was processed using multiple linear regression through the Eviews program. From the results of this study it was found that personal and psychological variables had a significant influence on the dependent variable, namely the use of digital wallets. It is hoped that further researchers will be able to examine more deeply and take more samples so that the results obtained are more accurate.